2001
DOI: 10.1074/jbc.m009103200
|View full text |Cite
|
Sign up to set email alerts
|

Testis Hormone-sensitive Lipase Expression in Spermatids Is Governed by a Short Promoter in Transgenic Mice

Abstract: A testicular form of hormone-sensitive lipase (HSL tes ), a triacylglycerol lipase, and cholesterol esterase, is expressed in male germ cells. Northern blot analysis showed HSL tes mRNA expression in early spermatids. Immunolocalization of the protein in human and rodent seminiferous tubules indicated that the highest level of expression occurred in elongated spermatids. We have previously shown that 0.5 kilobase pairs of the human HSL tes promoter directs testis-specific expression of a chloramphenicol acetyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 40 publications
(56 reference statements)
3
32
1
Order By: Relevance
“…1). Moreover, we have shown that the human exon T1 5Ј flanking region conferred expression of a reporter gene only in testes of Tg mice (17). Therefore, it seems clear that the regulatory elements responsible for HSL expression in testis are distinct from those involved in AT.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…1). Moreover, we have shown that the human exon T1 5Ј flanking region conferred expression of a reporter gene only in testes of Tg mice (17). Therefore, it seems clear that the regulatory elements responsible for HSL expression in testis are distinct from those involved in AT.…”
Section: Discussionmentioning
confidence: 95%
“…The 3.9 kb mRNA encodes a 1,076 amino acid protein that contains a unique NH 2 -terminal region encoded by exon T1. The first 95 bp of the 5 Ј -flanking sequence upstream of exon T1 confers expression of a reporter gene exclusively in testis of transgenic (Tg) mice (17). The 3.3 kb mRNA encodes a protein that is identical to the adipocyte HSL form.…”
Section: Supplementary Abstract Adipocyte • Fat Mobilization • Transmentioning
confidence: 99%
“…To date, there is little information on the mechanisms controlling tissue-specific expression of HSL. We have shown that the first 95 bp of human exon T1 5Ј-flanking region conferred expression of a reporter gene exclusively in testis of transgenic mice (27). Exon B 5Ј-flanking region contains an active promoter with an E-box and two GC-boxes as functional cis-acting elements (28).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to 10 exons that are transcribed into HSL mRNA in all human and mouse tissues, alternative exon usage results in a significant variation in the 5′-region of HSL transcripts (37)(38)(39)(40). In adipose tissue, adrenal gland, and ovary, HSL transcription starts from multiple exons (exons A, B, C, D, or exon 1) within a 13 kb region.…”
Section: Hsl Enzymologymentioning
confidence: 99%